The Coming Revolution in Political Economy: Money Creation, Mankiw and Misguided Macroeconomics - Tim Di Muzio; Leoni Noble (Real-World Economics Review, 2017)
The aim of this article is to challenge one of the principal received truths in the field of Economics: the way that new money is created. We also aim to go further and argue that a proper understanding of how new money is created has such devastating consequences that it heralds no less than a coming revolution in how we understand political economy and future possibilities. Our main argument is that the received truth of the fractional reserve theory or `money multiplier' model taught in most economics textbooks cannot explain the expansion of the money supply by logic, simple math and by basic bank accounting practices. To demonstrate our argument we rely on Mankiw's `Macroeconomics' and his chapter explaining to students how new money is created. We use Professor Mankiw's textbook because of its widespread use as an introductory text to macroeconomics. Our second argument is that the vast majority of new money is actually created by banks when they make loans. The article concludes with a discussion of some of the major consequences of allowing private social forces to issue new money as debt.
Keywords: 330; capitalism; fractional reserve; inequality; money; Mankiw; political economy